Scintigraphic evaluation of colon targeting pectin-HPMC tablets in healthy volunteers - UĞURLU, TİMUÇİN (ELSEVIER SCIENCE BV, 2009)
The in vivo evaluation of colon-targeting tablets was conducted in six healthy male volunteers. A pectin-hydroxypropyl methylcellulose coating was compressed onto core tablets labelled with 4 MBq (99m)Tc-DTPA. The tablets released in the colon in all subjects: three in the ascending colon (AC) and three in the transverse colon (TC). Tablets that released in the TC had reached the AC before or just after food (Group A). The other three tablets released immediately upon AC entry at least 1.5 h post-meal (Group 13). Release onset for Group B was earlier than Group A (343 min vs 448 min). Group B tablets exhibited a clear residence period at the ileocaecal junction (ICJ) which was not observed in Group A. Prolonged residence at the ICJ is assumed to have increased hydration of the hydrogel layer surrounding the core tablet. Forces applied as the tablets progressed through the ICJ may have disrupted the hydrogel layer sufficiently to initiate radiolabel release. Conversely, Group A tablets moved rapidly through the AC to the TC, possibly minimising contact times with water pockets. Inadequate prior hydration of the hydrogel layer preventing access of pectinolytic enzymes and reduced fluid availability in the TC may have retarded tablet disintegration and radiolabel diffusion. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Compression-coated tablets; Colon-specific drug delivery; Gamma scintigraphy; HPMC; Pectin; RELEASE RATE MODULATION; BINARY POLYMER SYSTEM; FILM-COATED TABLETS; IN-VITRO EVALUATION; DRUG-DELIVERY; MATRIX TABLETS; TRANSIT; SITE; FORMULATIONS; TIME